Emulsifying properties of Hydrolysates isolated from soybean protein - Panizzolo, Luis Alberto (2015)
We have developed new surfactant agents based on hydrolyzed soybean proteins using papain, and we have studied their ability to form and stabilize emulsions. The interfacial behavior and the emulsifying properties were correlated to the structural changes that the proteins underwent. The hydrolysis reaction was stopped by dropping to pH 2 in one case, or rapidly dropping the temperature to -18ºC in the other. The structural and functional properties of the obtained products depended on the way the papain hydrolysis of the soy proteins was stopped. Hydrolysis did not have a beneficial effect on the emulsifying properties of those hydrolysates that were stopped by freezing. For all the degrees of hydrolysis we studied, the emulsifying properties of the isolates were significantly improved when the hydrolysis reaction was stopped by dropping to pH 2.